Synchronous method and mechanism of asphalt-aggregate separation and regeneration of reclaimed asphalt pavement. (16th May 2023) - Liu, Chaochao; Zhao, Bo; Xue, Yanhua; He, Yaxuan; Ding, Sha; Wen, Yiyi; Lv, Songtao
Highlights: The method of asphalt-aggregate separation and synchronous regeneration of RAP with bio-oil as solvent is proposed. There is no false particle size phenomenon in the stripped aggregate after asphalt-aggregate separation, and the coarse aggregate remains intact. The residue on the surface of stripped aggregate forms a pre-coating on the stripped aggregate, which improves the bonding performance of asphalt and stripped aggregate. Abstract: The objective of this paper is to propose a separation technology for asphalt and aggregates of reclaimed asphalt pavement (RAP) materials with bio-oil as a solvent, which could significantly improve the recycling rate and quality of RAP. The byproducts of asphalt-aggregates separation of RAP are the stripped aggregate and the blends of bio-oil and old asphalt (BBOA). The stripped aggregates could be used as new aggregates. Based on the superior compatibility of bio-oil and asphalt, and the regeneration effect of bio-oil on old asphalt, the BBOA could be used as raw material for asphalt or liquid asphalt production. Through 60 °C viscosity, Fourier transforms infrared spectroscopy (FTIR), fluorescence microscope (FS), scanning electron microscope (SEM), contact angle, and adhesion test, established the relationship between the separation effect and the temperature, time, the mass ratio of RAP to bio-oil. The results show that the optimum temperature for asphalt-aggregate separation is about 110 °C, and the optimum mass ratio of RAP to bio-oil is 4:1 ∼ 5:1. The residue on the stripped aggregate surface is consistent with the characteristic peak of BBOA. BBOA can form pre-coating on the stripped aggregate and improve the bonding performance of asphalt and stripped aggregate. The stripped aggregate obtained after asphalt-aggregate separation has no false particle size phenomenon, and the coarse aggregate remains intact. The residue on the surface of stripped aggregate increases with the decrease in aggregate particle size. The stripped aggregate becomes oil sand when the aggregate particle size is less than 1.18 mm.